2020
DOI: 10.1021/jacs.0c09230
|View full text |Cite
|
Sign up to set email alerts
|

Transcription and Reverse Transcription of an Expanded Genetic Alphabet In Vitro and in a Semisynthetic Organism

Abstract: Through the development of unnatural base pairs that are compatible with native DNA and RNA polymerases and the ribosome, we have expanded the genetic alphabet and enabled in vitro and in vivo production of proteins containing noncanonical amino acids. However, the absence of assays to characterize transcription has prevented the deconvolution of the contributions of transcription and translation to the reduced performance of some unnatural codons. Here we show that RNA containing the unnatural nucleotides is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 13 publications
0
16
0
Order By: Relevance
“…1 ). This asymmetric, strand-specific selection is distinct from that in DNA replication 13 , as well as transcription by T7 RNAP 14 . Notably, there are several key differences between single subunit T7 RNAP and multi-subunit RNA Pol II.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…1 ). This asymmetric, strand-specific selection is distinct from that in DNA replication 13 , as well as transcription by T7 RNAP 14 . Notably, there are several key differences between single subunit T7 RNAP and multi-subunit RNA Pol II.…”
Section: Discussionmentioning
confidence: 86%
“…In the E. coli semi-synthetic organism (SSO), the unnatural nucleotides are transcribed by the heterologously expressed single subunit RNA polymerase from T7 bacteriophage. Recent studies suggest that the fidelity of transcription by the bacteriophage polymerase in the SSO does not limit the fidelity of unnatural protein production 14 , and in vitro, transcription of a template containing d5SICS with NaM proceeded with fidelity that is comparable to a natural pair’s transcription and the transcription of a template containing dNaM with 5SICS proceeded with fidelity of 92% 2 , 5 , 14 , 15 , the mechanism of the transcription of DNA containing UBPs has not been extensively investigated as the mechanism of replication. Moreover, current efforts to optimize the E. coli SSO or to create semi-synthetic eukaryotes would be facilitated utilizing their cellular multi-subunit RNA polymerases, which bear limited structural or functional homology to the single subunit polymerases.…”
Section: Introductionmentioning
confidence: 99%
“…While extensive characterization of unnatural DNA replication fidelity, kinetics of insertion, and mutation profiles have been performed, less information is known about the UBP in RNA. Reverse transcription analysis of T7 RNAP transcription products from the bacterial SSO revealed asymmetric transcription fidelity‐dTPT3 transcribing NaM occurs at higher fidelity than dNaM transcribing TPT3 [35] . Similarly, steady state kinetics revealed transcription by eukaryotic RNA Pol II of dTPT3 with NaM proceeded with high fidelity, whereas transcription of dNaM with TPT3 competes with natural ribonucleotides [36] .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they confirmed that at least three of the codon-anticodon interactions, AXC-GYU, GXC-GYC, and AGX-XCU, are orthogonal to each other, allowing for simultaneous decoding in the SSO ( Fischer et al, 2020 ). By measuring the transcription fidelity in vivo , they found that the decoding at the ribosome is more sensitive than transcription ( Zhou et al, 2020 ). This might be because the variable codon performance is the total output of the sequence-dependent translation efficiency, although the recognition of the codon-anticodon interaction might differ in eukaryotic cells ( Zhou et al, 2019 ).…”
Section: Genetic Code Expansion Using Ubp Systemsmentioning
confidence: 99%